Investigating Long-Run and Short-Run Dynamics of Palm Oil Production with Key Factors Using the VECM Method - Lathifah Zahra; Gustriza Erda (Indonesian Operations Research Association (IORA), 2025)
This study investigates the long-run and short-run relationships among palm oil production, rainfall, the number of bunches per palm (NOB), and average bunch weight (BTR) using the Vector Error Correction Model (VECM). Monthly data from 2015 to 2024 obtained from PT Perkebunan Nusantara IV (PTPN IV) Regional III, Sei Rokan Estate, were analyzed. Descriptive statistics indicate high variability in rainfall and relatively balanced distributions for production, NOB, and BTR. The Augmented Dickey-Fuller (ADF) test confirmed that all variables became stationary after first differencing, and the Johansen cointegration test identified three cointegrating relationships, suggesting both short-run and long-run linkages among variables. The VECM estimation results reveal positive long-run relationships for palm oil production (ECT = 0,052), rainfall (ECT = 0,090), and NOB (ECT = 0,042), indicating that these variables move toward long-run equilibrium in the same direction. In the short run, previous rainfall significantly affects both current palm oil production and NOB, with coefficients of 0,203 and 0,178, respectively, highlighting the critical role of rainfall fluctuations in influencing short-term productivity and fruit development. Model evaluation using the Root Mean Square Error (RMSE) shows low prediction errors across all variables, with rainfall having the highest RMSE (1,334) and NOB the lowest (0,962), confirming the model’s strong predictive performance. Overall, the findings demonstrate that the VECM approach effectively captures both long-run equilibrium and short-run dynamics among key determinants of palm oil productivity in the Sei Rokan plantation.